Penerapan Pencatatan Keuangan Berbasis SAK ETAP dengan Pendekatan Analisis SWOT pada UMKM di Kota Kupang - Helda Marlin Ala; Boy Supriana Efendi (Jurnal Inovasi Kebijakan, 2019)
This research aims to determine the financial recording process based on SAK ETAP for the development of Micro, Small and Medium Enterprises (MSMEs) in Kupang City. The method used in this research is a qualitative approach, and the subject of this research is the MSME Business Owner in Kupang City. The data analysis technique used is qualitative analysis, which is done by collecting triangulation data, and the SWOT analysis technique is used in the systematic identification of various factors and the formulation of the SAK ETAP-based financial recording process in a company. The findings of this research indicate that the accounting process that starts from the recording process, balance sheet, income statement, statement of changes in equity, and cash flow statement in order to support the use of financial statements based on SAK ETAP cannot be carried out properly as a strength of an MSME in providing financial information for evaluating performance and measuring MSME profit and loss for one period.